Fast identification of flavonoids in the roots of Sophora flavescens by on-flow LC-NMR - Kim, Su Jin; Kim, Sang Min; Kim, Min Cheol; Kang, Suk Woo; Um, Byung Hun (ACADEMIC JOURNALS, 2010)
Sophora flavescens Ait (Leguminosae) is a Chinese herbal medicine. Sophorae radix, the dried roots of S. flavescens, has been used for various diseases including atherosclerosis and arrhythmias. For the direct identification of the compounds present in Sophorae radix, the hyphenated LC-NMR technique has been applied. WET solvent suppression and scout scan techniques were used to suppress solvent peaks in on-flow LC-NMR experiment. Six prenylflavonoids were identified successfully as kushenol U (1), kurarinone (2), sophoraflavanone G (3), leachianone A (4), kuraridin (5) and kushenol A (6).
Keywords: ANTIOXIDANT